Pelatihan Diversifikasi Produk Olahan Berbahan Dasar Pisang Lokal Sentani di Kampung Yahim, Distrik Sentani, Kabupaten Jayapura, Papua - Lisye I. Zebua; Vita Purnamasari; Jepron W. Wenda; Meiland A. Ronsumbre; Widiastuty Widiastuty; Triwiyono Triwiyono (LPPM Uncen, 2025)
Banana is a popular crop that can grow in almost all types of agroecosystems. Banana fruit can be used as an alternative staple food because it contains high carbohydrates, so it can replace some of the consumption of rice and wheat. For the Sentani people, the banana plant has an important cultural value. Apart from being consumed and sold in the market, local bananas are often used as a means of payment for dowries. The people of Yahim Village in Sentani District recognize five local banana varieties, namely: Kheja, Hoyombi, Ratake, Ramaohulu, Habili, Ebulu, Molonsi, and Ramehaye. The objectives of this service activity are: to introduce local banana-based processed food products that have high selling value to the people of Yahim Village and to train mothers and young women to process various types of processed food products made from local Sentani bananas in Yahim Village, Sentani District. The service method used in this training consists of three stages, namely preparation, consultation, short practice, mentoring and evaluation. The results and achievements of this service activity are that the women in Yahim village can produce banana doughnuts, banana sticks and banana chips. Then they can package these products in creative and innovative packaging. The results of the activity evaluation showed that 85% of the participants could understand and absorb the training materials, 90% of the participants were skilled in processing local Sentani bananas, and 90% of the participants stated that this service activity was very useful.